DEVELOPMENT OF CORNER CLOCK LEARNING MEDIA TO IMPROVE ANGULAR MEASUREMENT SKILLS AND SPATIAL ABILITY OF SDN KEBAYUNAN STUDENTS DEPOK CITY - Prapti Wulandari; Dian Novita (Schola, 2025)
Education is a continuous process that plays an important role in the development of students' cognitive abilities, including through mathematics learning in elementary school. One of the essential geometry materials that is still considered difficult by students is angle measurement. The low understanding of concepts and students' spatial abilities in the material is caused by the abstract nature of mathematics and the lack of use of concrete learning media. Therefore, this study aims to develop and test the validity, practicality, and effectiveness of Corner Clock  learning media in improving the angular measurement ability and spatial ability of elementary school students. This research uses a Research and Development (R&D)  approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subject of the study is a third-grade student of SDN Kebayunan Depok City. Data was collected through tests of angular measurement ability and spatial ability, student response questionnaires, interviews, and documentation. The results of the study show that the Corner Clock media is declared valid by experts, practical based on positive student responses, and effective in improving learning outcomes. The average pretest score of 60.29 increased to 81.79 in the posttest. In addition, the use of Corner Clock media is able to increase student involvement, help visualize corners concretely, and train spatial skills through manipulative activities. Thus, Corner Clock learning media is suitable for use as an alternative to mathematics learning media in angle measurement materials in elementary schools and has the potential to improve the quality of meaningful and contextual learning.